2015
DOI: 10.1111/ajt.13419
|View full text |Cite
|
Sign up to set email alerts
|

A Registry Analysis of Damage to the Deceased Donor Pancreas During Procurement

Abstract: Surgical injury to the pancreas is thought to occur commonly during procurement. The UK Transplant Registry was analyzed to determine the frequency of pancreatic injuries, identify factors associated with damage, and assess the impact of injuries on graft survival. Twelve hundred ninety-six pancreata were procured from donation after brain death donors, with 314 (19.5%) from donation after circulatory death donors. More than 50% of recovered pancreata had at least one injury, most commonly a short portal vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…The use of bioreactor technology to co‐localize cells across species barriers is novel and has important therapeutic implications. The limited availability of human cadaveric material is circumvented by use of porcine tissue, which is proposed to become a feasible source for human implantation following adoption of CRISPR‐based gene editing to inactivate porcine endogenous retroviruses . The incorporation of AEC to porcine islet grafts adds localized anti‐inflammatory and immunomodulatory properties that reduce xenogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bioreactor technology to co‐localize cells across species barriers is novel and has important therapeutic implications. The limited availability of human cadaveric material is circumvented by use of porcine tissue, which is proposed to become a feasible source for human implantation following adoption of CRISPR‐based gene editing to inactivate porcine endogenous retroviruses . The incorporation of AEC to porcine islet grafts adds localized anti‐inflammatory and immunomodulatory properties that reduce xenogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that a high proportion of pancreases that are offered for allocation are not transplanted, often due to perceived unfavorable donor characteristics (e.g., age, BMI, elevated serum amylase) or the appearance or consistency of the pancreas at the time of recovery of organs or bench work . Furthermore, the pancreas is more vulnerable to intraoperative injury than other abdominal organs during recovery of organs . As a result, the conversion rate from potential pancreas donor to implantation in a recipient is low; registry data show that only 70% of potential donor pancreases offered for donation are recovered, and of these, a further 30–50% are discarded after recovery of organs has been completed .…”
Section: Discussionmentioning
confidence: 99%
“…for pancreas, 34 but the rate of discard resulting from surgical injury for these organs is 0.8-1.4% for kidney, 32,35 .8-6.6% for liver, 33,35 and 10-13% for pancreas. 35,36 Thus, these data indicate that albeit common, procurement-related injury is rarely irremediable or transplant-defining.…”
Section: P-valuementioning
confidence: 99%